Online Support Seeking and Breast Cancer Patients: Changes in Support Seeking Behavior following Diagnosis and Transition off Cancer Therapy. Issue 6 (12th May 2021) - Mikal, Jude P.; Beckstrand, Michael J.; Grande, Stuart W.; Parks, Elise; Oyenuga, Mosunmoluwa; Odebunmi, Tolulope; Okedele, Olasunmbo; Uchino, Bert; Horvath, Keith
ABSTRACT: Transitions in breast cancer care are associated with significant increases in stress and anxiety, and this stress can negatively impact mental and physical health. Social support has been shown to alleviate such distress, but whether, how, and how often social support is accessed through existing support networks is unclear. Our study examines changes in social media use following breast cancer diagnosis and treatment, using hand-coded longitudinal data from 30 breast cancer survivors' Facebook pages for the 6 months surrounding cancer diagnosis and for the 6 months surrounding transition off cancer therapy. Results revealed that following diagnosis, there was a significant increase in posting behavior and self-disclosure. However, this increase in posts did not correspond to an increase in support requests. In addition, while participants' primary support requests were for resources, support provided tended to be lower-cost emotional support. Finally, temporal maps indicated that participants started off increasing their engagement but withdrew over time. Our findings suggest that Facebook offered participants a platform for continued social engagement and self-disclosure – but showed several indications that support was principally low-effort, limited quality, and ill-fitting.